The Utilization of FermentedTuri Leaf Meal (Sesbania grandiflora) in Artificial Diet on Growth of Jelawat (Leptobarbus hoeveni) - Riski Rahmadana; Indra Suharman; Adelina Adelina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis Research was conducted from Desember 2016 to Februari 2017. The aim of this research was to know the effect of using fermentedTuri leaf meal in artificial diet on growth and feed efficiency of jelawat (Leptobarbus hoeveni). This research used completely randomized design (CRD) with one factor, five treatments and three replications. This research used fish with initial average weight of 14,9 g. Fish were reared innet cage of 1.0x1.0x1.0 (m3) with the stocking density of 20 fish/net cage. Feeding trials were replacing soybean meal with fermentedturileaf meal applied to P0 (0 : 100%) as a control diet, P1 (5 : 95%), P2 (10 : 90%), P3 (15 : 85%) and P4 (20 : 80%) for 30 % protein content. The result showed that fermentedturi leaf meal give significant effect (P<0,05) on growth, feed efficiency and protein retentions. This result of this study suggest that fermentedturi leaf meal protein can replace up to 15% of the soybean meal in practical diet for jelawat without any adverse performance. Keyword :Diet, Growth, Leptobarbus hoeveni,Sesbania grandiflora, Subtitution